Implementing an electronic payment system: getting things done! - Zainol, Zaini; Mokhtar, Norsyahida (IIUM Press, 2022)
This case study presents the challenges and critical success factors in JomPAY implementation in a local authority in Putrajaya. System failures, stakeholders' resistance to change and third-parties operational issues were among the challenges faced by the local authority in implementing the system. The project champion‟s credibility and technical skills play an important role in making sure the implementation is a success.